2019
DOI: 10.14302/issn.2574-450x.jom-18-2484
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Fennel (Foeniculum Vulgare) in Treating Obesity in Rats

Abstract: Obesity is associated with a number of serious medical complications, which are often referred to as the “insulin resistance syndrome”. The aim of the present study was performed to investigate the possible interaction between a conventional drug used for management of cholesterol and traditional herbal remedies on the obesity. This was carried through out: through estimation of blood test; Estimation of serum tests; Determination of oxidative stress biomarkers and the antioxidant enzymes activities in the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
3
8
0
1
Order By: Relevance
“…A previous study reported that body weight was lower in the FEO-inhaled group than in the control group (p < 0.05), which was similar to our results [22]. Moreover, a previous study reported that the intake of fennel affected decreases in body weight compared to the non-intake of fennel [11]. In addition, another study reported that trans-anethole, a major compound of fennel, increased the activation of AMP-activated protein kinase (AMPK) and peroxisome proliferator-activated receptor α (PPARα) in adipocytes, thereby decreasing body fat accumulation and increasing body weight [23].…”
Section: Food Intake Body Weight Body Composition and Lengthsupporting
confidence: 91%
See 2 more Smart Citations
“…A previous study reported that body weight was lower in the FEO-inhaled group than in the control group (p < 0.05), which was similar to our results [22]. Moreover, a previous study reported that the intake of fennel affected decreases in body weight compared to the non-intake of fennel [11]. In addition, another study reported that trans-anethole, a major compound of fennel, increased the activation of AMP-activated protein kinase (AMPK) and peroxisome proliferator-activated receptor α (PPARα) in adipocytes, thereby decreasing body fat accumulation and increasing body weight [23].…”
Section: Food Intake Body Weight Body Composition and Lengthsupporting
confidence: 91%
“…Inhalation of FEO showed no significant variation in ALT levels among all groups. On the other hand, the AST levels decreased in the FEO-inhaled groups compared to group H (p < 0.05), and there has been no significant negative effect of hepatotoxicity, and it may induce the suppression of hepatotoxicity according to the decreased AST levels [11,29].…”
Section: Plasma Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A recent studies showed that senna has antidiabetic effect, in addition to the laxative effect of sennosides and hence senna can control obesity 16&17 . Fennel decreases food intake and increases satiety by stimulating cholecystokinin release 18 . Celery and calendula were found to contain compounds that are effective in reducing obesity 19&20 .…”
Section: Resultsmentioning
confidence: 99%
“…Fennel seed shape is oval and has a strong scent, while the fruit has slightly sweet and slightly spicy. The seeds contain fiber and complex carbohydrates (Elghazaly et al, 2019). Fennel seeds were found to have a hypotensive effect, hepatoprotective, anti-inflammatory, antidementia, protective effect against ethanol induced gastric mucosal lesions, anticancer (Rezq, 2012).…”
Section: ‫النوعية‬ ‫التربية‬ ‫مجاالت‬ ‫في‬ ‫البحوث‬ ‫مجلة‬mentioning
confidence: 99%